STUDIES ON GENETIC PARAMETERS AND INTER-RELATIONSHIPS AMONG YIELD AND YIELD CONTRIBUTING TRAITS IN SORGHUM (SORGHUM BICOLOR L. MOENCH) - KUMAR, B. ARUN (The Bioscan, 2013)
Experiment was conducted on sorghum to study the genetic variability, association among the yield component traits, their direct and indirect effects on the yield. Genotypic coefficient of variation was played a major role for the expression of the traits ranged from 4.12 (seed set percent) to 25.29 (fodder yield). Heritability in narrow sense ranged from 50.00 (seed set percent, test weight) to 82.00 (grain yield). High genetic advance was observed for the traits, grain yield (485.19) and fodder yield (40.16) coupled with high heritability (82 and 86), indicating the preponderance of the non-additive gene action; suggesting that hybridization breeding will be effective. General the genotypic correlation was generally of higher magnitude than phenotypic correlation. Ear head length (0.454*) and fodder yield (0.441*) were positively and significantly associated with grain yield per hectare and grain yield per plant respectively at genotypic level, indicating increase in ear head length will increase the yield. Negative and significant association at genotypic level was noticed between days to 50% flowering and ear head breadth (-0.447*) and seed set per cent with ear head length (-0.603*) and fodder yield per plant (-0.497*). Days to 50% flowering (0.055 and 0.142), ear head length(0.177 and 0.028) and test weight (0.332 and 0.125) at both genotypic and phenotypic level have positive direct effect on yield indicating importance of these characters and can be strategically used to improve the yield of sorghum.